(untitled) (Trabalho & Educação, 2017)
In context of the expansion and internalization of higher education in Brazil, observed the growing number of university centers in small and medium-sized cities. At the Federal University of Paraná, this movement has began with the creation of campus Palotina (PR) and thereafter creating two poles in the state coast. This article aims to relate the undergraduate courses offered in these campuses between 2008 and 2016 and the most employment-generating economic activities in their respective microregions. As a methodological procedure, the research is classified as descriptive, bibliographical and documentary, since has used UFPR’s activity reports and data from the Annual Social Information Ratio (RAIS) to extract necessary information. As a result, it has been observed that the Veterinary Medicine and Agronomy courses are aligned with regional economic activities. On the coast case, there are few courses directly related with activities that generate the most employment in the micro-region. In both regions there is a potential supply of courses in the chemical and food field. ___ No contexto da expansão e interiorização do ensino superior no Brasil, observa-se o crescimento do número de polos universitários em pequenas e médias cidades. Na Universidade Federal do Paraná, esse movimento iniciou-se com a criação do campus Palotina (PR) e, posteriormente, com a criação de dois polos no litoral do estado. O presente artigo tem por objetivo relacionar os cursos de graduação ofertados nesses campi, entre os anos de 2008 e 2016, com as atividades econômicas que mais geraram empregos nas respectivas microrregiões. Como procedimento metodológico, a pesquisa é classificada como descritiva, bibliográfica e documental, visto que utiliza os relatórios de atividades da UFPR e dados da Relação de Informações Anuais Sociais (RAIS) para extrair informações necessárias. Como resultado, observa-se que os cursos de Medicina Veterinária e Agronomia estão alinhados com as atividades econômicas regionais. Já no caso do litoral há poucos cursos relacionados diretamente com as atividades que mais geram empregos na microrregião. Em ambas as regiões há um potencial de oferta de cursos na área química e alimentar.